2022
DOI: 10.3389/fpubh.2022.931306
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine uptake among people who inject drugs in Tijuana Mexico

Abstract: Background:SARS-CoV-2 prevalence is elevated among people who inject drugs (PWID). In Tijuana, Mexico, COVID-19 vaccines became available to the general population in June 2021, but uptake among PWID was <10%. We studied COVID-19 vaccine uptake among PWID in Tijuana following implementation of a pop-up vaccination clinic.MethodsBeginning in October, 2020, PWID in Tijuana aged ≥18 years were enrolled into a longitudinal cohort study. At baseline and semi-annually, participants underwent interviewer-admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
1
18
1
Order By: Relevance
“…Since more than one third of vaccinated PWID had previously been hesitant towards COVID-19 vaccines and half of unvaccinated PWID expressed interest in being vaccinated, our results suggest that targeted efforts to thwart disinformation and medical distrust could improve COVID-19 vaccination in this population. Our study and others found greater COVID-19 vaccination uptake in circumstances where PWID have trust in the medical establishment and when they have received preventive services or health care for other conditions [12] , [13] , [15] , [27] . Resources should be allocated to integrate COVID-19 vaccination into programs that are frequented and trusted by PWID, which includes SSPs and other harm reduction programs, homeless shelters, health fairs and drug treatment centers.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…Since more than one third of vaccinated PWID had previously been hesitant towards COVID-19 vaccines and half of unvaccinated PWID expressed interest in being vaccinated, our results suggest that targeted efforts to thwart disinformation and medical distrust could improve COVID-19 vaccination in this population. Our study and others found greater COVID-19 vaccination uptake in circumstances where PWID have trust in the medical establishment and when they have received preventive services or health care for other conditions [12] , [13] , [15] , [27] . Resources should be allocated to integrate COVID-19 vaccination into programs that are frequented and trusted by PWID, which includes SSPs and other harm reduction programs, homeless shelters, health fairs and drug treatment centers.…”
Section: Discussionsupporting
confidence: 49%
“…Since we also found that participants who knew more people who had received COVID-19 vaccines had greater vaccine uptake, public health messaging for PWID should focus on dispelling conspiracy theories and fostering health literacy by enlisting peers, trusted community opinion leaders and outreach workers [28] . In a recent study in Tijuana, significantly higher COVID-19 vaccination rates occurred among PWID who attended a “pop-up” vaccine clinic that was staffed by medical professionals possessing experience working with substance using populations [15] . Similar approaches to increase COVID-19 vaccination should be offered at locations where PWID seek services, such as drug treatment programs, SSPs, soup kitchens, homeless shelters and community health fairs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, delivery of vaccine at such services requires dedicated funding to increase immunisation service delivery capacity [49]. In the absence of such funding, referral to a public vaccination site via street outreach services has also been shown to increase uptake among people who inject drugs [50].…”
Section: Discussionmentioning
confidence: 99%